Pengaruh Ukuran Perusahaan, Kepemilikan Manajerial, dan Faktor Lainnya terhadap Manajemen Laba - William Yehezkiel; Sugiarto Prajitno (Media Bisnis, 2022)
The purpose of this research was to obtain empirical evidence regarding the effect of firm size (SIZE), managerial ownership (MOWN), liquidity ratio (LIQ), leverage (LEV), cash flow from operations (CFO), profitability ratio (ROA), and firm age (AGE) to earnings management (DAC). The population taken from this research are 462 non-financial companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 to 2020. The sample in this study used 87 companies with a total of 261 companies data used. The method used in sampling in this research uses purposive sampling with six sample criteria. While the technique used in this research is multiple regression model. The result of this study indicate that firm size variable affect on earnings management while managerial ownership, liquidity ratios, leverage, cash flow from operations, profitability ratios, and firm age have no affect on earnings management.